2023
DOI: 10.3390/polym15112525
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Self-Polymerized Polydopamine Coating on Mechanical Properties of Polylactic Acid (PLA)–Kenaf Fiber (KF) in Fused Deposition Modeling (FDM)

Sanusi Hamat,
Mohamad Ridzwan Ishak,
Mohd Sapuan Salit
et al.

Abstract: This research examines the impact of self-polymerized polydopamine (PDA) coating on the mechanical properties and microstructural behavior of polylactic acid (PLA)/kenaf fiber (KF) composites in fused deposition modeling (FDM). A biodegradable FDM model of natural fiber-reinforced composite (NFRC) filaments, coated with dopamine and reinforced with 5 to 20 wt.% bast kenaf fibers, was developed for 3D printing applications. Tensile, compression, and flexural test specimens were 3D printed, and the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
(141 reference statements)
0
7
0
Order By: Relevance
“…Besides, elongations at break of PLA films coated with Zn(OH) 2 paint and GO-ZnO paint were lower than that of blank PLA films. In scientific literature, coating effects on the decrease of materials elongation were also reported [67][68][69]. During tensile process, cracks appreared in the brittle coatings and propagated into the substrates.…”
Section: Mechanical Tensile Property Of Pla Based Thin Filmsmentioning
confidence: 94%
“…Besides, elongations at break of PLA films coated with Zn(OH) 2 paint and GO-ZnO paint were lower than that of blank PLA films. In scientific literature, coating effects on the decrease of materials elongation were also reported [67][68][69]. During tensile process, cracks appreared in the brittle coatings and propagated into the substrates.…”
Section: Mechanical Tensile Property Of Pla Based Thin Filmsmentioning
confidence: 94%
“…A particularity of this unconventional process is the adhesion of the coating using polymer materials. Layer adhesion refers to the cohesive bonds formed between consecutive layers of material during the additive manufacturing process, ensuring the structural integrity and stability of the printed object [25][26][27][28]. with a Grid infill, the Flexure load at Tensile Strength recorded a value of 300 N. Utilizing a Gyroid infill pattern resulted in recorded forces reaching a value of 379 N, whereas the employment of a Triangles infill pattern yielded forces measuring at 232 N. All values are presented in Tables 3 and 4.…”
Section: Analisys Of the Lateral Thigh Pivotal Componentsmentioning
confidence: 99%
“…A particularity of this unconventional process is the adhesion of the coating using polymer materials. Layer adhesion refers to the cohesive bonds formed between consecutive layers of material during the additive manufacturing process, ensuring the structural integrity and stability of the printed object [25][26][27][28]. In the second test, the joint consisted of components obtained through 3D printing utilizing PLA as the material.…”
Section: Analisys Of the Lateral Thigh Pivotal Componentsmentioning
confidence: 99%
“…Feng et al [25] found that the interfacial interaction between filler and polyarylene ether nitrile was enhanced by a coreshell structural composite (MoS 2 @PDA). Sanusi Hamat et al [26] found that a coupling agent (PDA) could increase the tensile Young's modulus, flexural Young's modulus, and compressive stress of kenaf fibers and the PLA matrix by 13.4%, 15.3%, and 30%, respectively. Therefore, the use of MoS 2 @ PDA core-shell structure nanoparticles doped with modified PI materials is expected to further enhance the mechanical and friction properties of the composites, as well as effectively improve the electrical insulation properties of the composites.…”
Section: Introductionmentioning
confidence: 99%